BaGe8As14: a semiconducting sodalite-type compound. Issue 11 (11th January 2021) - Weippert, Valentin; Chau, Thanh; Witthaut, Kristian; Eisenburger, Lucien; Johrendt, Dirk
Abstract : The new semiconducting sodalite-type BaGe8 As14 compound exhibits a narrow band gap, low resistivity and partially disordered atom positions as good prerequisites for a thermoelectric material. Abstract : A new sodalite-type compound, namely BaGe8 As14 was synthesized via solid-state reactions and structurally characterized with single crystal X-ray diffraction (space group I 4̄3 m ). Vertex-sharing GeAs4 -tetrahedra form β-cages with additional Ge/As-mixed sites located slightly above or below the six-membered rings. The structure is similar to the borate mineral rhodizite. Barium atoms are disordered due to a slight shift off the centers of large β-cages. This partially disordered structure together with a narrow bandgap of 0.43 eV in line with low resistivity (2 × 10 −2 Ω cm), and a high carrier concentration (1.6 × 10 20 cm −3 ) at 300 K qualifies BaGe8 As14 as a potential thermoelectric material.